2002
DOI: 10.1210/jcem.87.7.8695
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Spillover from Human Adipose Tissue before and after a 72-Hour Fast

Abstract: Adipose tissue lipolysis is at least in part stimulated by the sympathetic nervous system (SNS). Although there is a generalized decrease in SNS activity with fasting, the rate of lipolysis during fasting increases. The aim of this study was to determine whether there is an association between activation of sympathetic nerves innervating adipose tissue and the increase in lipolysis seen during fasting in humans. We used the isotope dilution technique to measure regional norepinephrine spillover from abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
1
22
1
3
Order By: Relevance
“…Caloric restriction also enhances lipolysis by increasing beta-adrenergic receptors in the adipose tissue [30,31] and, in normal body weight subjects, the norepinephrine spillover from the fat depots [32]. In obese subjects, a blunted sympathetic activation in the adipose tissue district could lead to defective lipolysis and, by consequence, to a smaller weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction also enhances lipolysis by increasing beta-adrenergic receptors in the adipose tissue [30,31] and, in normal body weight subjects, the norepinephrine spillover from the fat depots [32]. In obese subjects, a blunted sympathetic activation in the adipose tissue district could lead to defective lipolysis and, by consequence, to a smaller weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that fasting increases norepinephrine spillover selectively from the adipose tissue; 25 furthermore, the beta-adrenergic-stimulated lipolysis is enhanced during hypocaloric diet: 9 these phenomena could be particularly evident in patients with a high degree of sympathetic reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ATBF increases in periods of starvation and postprandially. 50,51 Interestingly, the postprandial rise in ATBF is not a direct insulin effect but is mainly mediated through catecholamines and nitric oxide. 52,53 ATBF changes of the abdominal fat depot have been well studied in different settings; however, little is known regarding ATBF regulation in the lower-body fat depot.…”
Section: Fatty Acid Storage and Releasementioning
confidence: 99%